Religious Fanaticism and Science Reflected in Sebastian Lelio’s The Wonder (2022) - Maftukhah Dian Mutiari Raiz; Atinia Hidayah (Metaphor, 2024)
This research is conducted to analyze the form of religious fanaticism of Irish society in 1862 depicted in Sebastian Lelio's The Wonder (2022) and the conflict that occurred between science and religion in the film The Wonder (2022) using the Roland Barthes model semiotic theory. There are two problem statements that the researcher uses in this study, the first is how is religious fanaticism represented in Irish society in 1862 in Sebastian Lelio's The Wonder (2022)? Second, how is conflict between science and religion represented in Sebastian Lelio's The Wonder (2022)? The researcher uses a qualitative method in answering the problem formulation. The theories and approaches used in this study are the semiotic theory of the Roland Barthes model, fanaticism, Christian Fanaticism, and the conflict between science and religion. This research includes data collection procedures and data analysis procedures. This study's results show signs of religious fanaticism caused by church authority and fundamentalism, and conflict between science and religion because of the difference of opinion between rational thought and traditional thought based on religious rituals.